Effect of moderate electric field in the physical and transport properties of chitosan coatings - Souza, B. W. S. (2009)
Edible films and coatings can provide additional protection for food, while being a fully biodegradable, environmentally friendly packaging system. Preliminary works have shown that the presence of a moderate electric field during the preparation of chitosan coating solutions may influence e.g. their transport properties. The aim of this work was to determine the effect of field strength on functional properties of chitosan coatings (obtained from lobster of the Cuban coasts). Four different field strengths (50,100,150, 200 V·cm-1) were applied during the preparation of the film forming solution, films were cast and, for each electric treatment, the water vapor, O2 and CO2 permeabilities of the films were determined, together with their solubility in water. The films were also analysed using scanning electron microscopy (SEM) and X-ray diffractometry (XRD).The results showed that the electric field has statistically significant effects on films transport properties (which e.g. for water vapour permeability, varied from 0.3228 to 0.2667(g.(m.day.atm)-1)) and structure, a positive correlation having been found between the water vapor, O2 and CO2 permeability coefficients and the applied field strength. XRD indicated that when electrically treated, chitosan films exhibited a more ordered structure and a clearly higher crystallinity when compared with non-treated films. SEM micrographs evidenced that the surface morphologies of chitosan films were influenced by the electric field. In fact, the electric field treatment led to a structure with more regular layers as can be seen in the cross-sections of the films. These results clearly indicate that, when applied to the film-forming solution, the electrical field treatment may be a good tool to finely adjust the transport properties e.g. in taylor-made film formulations.